Vocabulary learning strategies of Saudi English major students: strategy use and gender - Al-Harbi, Jamilah; Engku Ibrahim, Engku Haliza (Science Publishing Corporation, 2018)
One of the major challenges that learners face during the process of foreign language learning is acquiring vocabulary. Thus, students need to employ various vocabulary learning strategies to acquire the vocabulary of a foreign language. The present study attempts to identify the vocabulary learning strategies employed by Saudi English major students. This study also aims to examine if there are differences between male and female students in the pattern and frequency of strategy use. Sixty-five first-year English major students of Majmaah University participated in the study. Their vocabulary learning strategies were measured using the Vocabulary Learning Strategy Survey. The results showed that students preferred cognitively less demanding strategies compared to the ones that required deeper cognitive processing. The most frequently used strategies were “I try to remember the word by repeating it for several times,” “I try to guess the meaning of the word from text/context” and “I learn new words when I interact with native speakers.” In general, social strategy is the most used strategy while memory strategy is the least used. The findings also showed that males preferred social strategy com- pared to females who preferred cognitive strategy and that two strategies (cognitive and memory strategies) showed significant differences between the two genders.